Psychosocial burden of caregivers taking care of children in the children's emergency room of two tertiary hospitals in Southeast Nigeria - Ikenna K Ndu; Chidiebere D I Osuorah; Ezinne I Nwaneli; Uchenna Ekwochi; Isaac N Asinobi; Kenechukwu K Iloh; Obinna C Nduagubam (Wolters Kluwer Medknow Publications, 2020)
Introduction: In this study, we sought to determine the severity of caregiving burden among caregivers of children presenting to the emergency room and analyze its associated predictors. Methods: This was a cross-sectional, study carried out on 332 caregivers of children admitted into the children emergency room (CHER) of two tertiary hospitals in Southeast Nigeria. A validated structured questionnaire was administered by an interviewer with the use of an interpreter where necessary. Results: A total of three hundred and thirty-two child-caregiver dyads were enrolled for this study. Fathers were 25.6%, mother 65.4%, and nonparent made up 9.0% of primary caregivers of child in index admission. The mean age of the enrolled children was 2.5 ± 1.9 years with age ranges of 1 month to 16 years. Male-to-female ratio was approximately 0.8. Two hundred and fifty-four (80.6%) of surveyed caregivers experienced high psychosocial burden. On the average, caregivers were faced with moderate burden in the CHER during care of their sick child with a mean caregiver burden score of 1.64 ± 0.67. Caregivers looking after independent children (odds ratio [OR]: 0.1, 95% confidence interval [CI]: 0.2-0.9; P = 0.05), partially dependent children (OR: 0.2, 95% CI: 0.3-0.9; P = 0.040), and those with someone assisting them in the care of admitted and/or children at home (OR: 0.5, 95% CI: 0.2-1.0; P = 0.050) were less likely to experience high psychosocial burden of care as compared with caregivers looking after dependent children and those with no assistance. Conclusion: There is a need to incorporate comprehensive psychosocial and instinctive support for caregivers during the care of their sick children in the emergency room.